Dissolved benthic phosphate, iron and carbon fluxes in the Mauritanian upwelling system and implications for ongoing deoxygenation. (January 2019) - Schroller-Lomnitz, U.; Hensen, C.; Dale, A.W.; Scholz, F.; Clemens, D.; Sommer, S.; Noffke, A.; Wallmann, K.
Abstract: Benthic fluxes of total dissolved phosphate (TPO4 3- ), dissolved iron (Fe 2+ ), and dissolved inorganic carbon (DIC) were determined in situ using benthic chambers at nine stations along a depth transect between 47 and 1108 m water depth at 18°N off Mauritania (NW Africa) during the upwelling season in 2014 (RV Meteor cruise M107). Bottom water oxygen (O2 ) concentrations were always ≥ 25 µM, and all fluxes (TPO4 3-, Fe 2+, DIC) were consistently directed from the sediments into the bottom water. The highest benthic TPO4 3- release of 0.2 ± 0.07 mmol m 2 d −1 was found at 47 m water depth (50 µM O2 ). The highest diffusive Fe 2+ flux of 0.03 mmol m 2 d −1, determined from porewater Fe 2+ concentrations, occurred at 67 m water depth (27 µM O2 ). This was much lower than the detrital Fe supply as indicated by constant Fe/Al ratios along the depth transect. TPO4 3- release rates decreased concurrently with DIC flux and water depth. A difference of up to one order of magnitude between benthic chamber and diffusive TPO4 3- fluxes indicated that the total TPO4 3- release was strongly enhanced by bioirrigation. The observed fluxes were similar to those measured during an earlier cruise in 2011, generally indicating comparable release rates during both upwelling seasons. Furthermore, ex situ oxygen manipulation experiments showed an increase of the nutrient release (e.g. TPO4 3-, Fe 2+ ) after seven days of anoxic bottom water conditions. The fluxes were enhanced by a factor of 1.4 for P and 7.3 for Fe compared to the measured release under natural conditions and reached values as high as those measured in the anoxic oxygen minimum zone off Peru. Our observations support the hypothesis that increasing deoxygenation of the oceans will likely enhance sedimentary TPO4 3- and Fe 2+ release and thus contribute to a positive feedback mechanism with increasing nutrient levels and increased ocean productivity. Highlights: Bioirrigation and bottom water percolation through permeable sediments enhance benthic TPO4 3- and Fe 2+ release additionally. Changes in bottom water oxygenation induce slight changes benthic TPO4 3- and Fe 2+ release rates measured in 2011 and 2014. Deoxygenation experiments imply enhanced TPO4 3- and Fe 2+ release at ongoing deoxygenation in the Mauritanian OMZ.